(untitled) (Journal of actual problems of jurisprudence, 2018)
A serious problem is the use of telecommunications by terrorists and other antisocial extremist organizations.Agitation, so for the collection, transfer funds, and coordinate their actions in an Internet page. This article discusses the above-mentioned problems of crime control in the field of information technology.As well as methods of dealing with IT crime. Key words: information technology,virus programs, electronic information.